New and First Records of Carybdeids Including Irukandji Box Jellyfish (Cnidaria: Cubozoa; Carybdeida) in the Coral Triangle (the Philippines) - Sheldon Rey Boco; Russel Christine B. Corcino; Christine Gloria Grace Capidos; Phuping Sucharitakul; Ram Yoro; Dennis Corpuz; Scott Tuason; Lemnuel V. Aragones (Thalassas: An International Journal of Marine Sciences, 2025)

Hitchhikers and anglers: novel ectosymbioses and predatory interactions with carybdeid box jellyfishes (Cnidaria: Cubozoa: Carybdeida) confirmed by citizen science and digital morphological analyses - Russel Christine B. Corcino; Sheldon Rey Boco; Phuping Sucharitakul; Joey Cabasan; Christine Gloria Grace Capidos; Ram Yoro; Dennis Corpuz; Scott Tuason; Lemnuel V. Aragones (Symbiosis, 2025)
Inter-species interactions with carybdeid cubomedusae (Cnidaria: Cubozoa) remain poorly understood for most members of this group. Given this knowledge disparity, we examined ectosymbiotic and predatory interactions with carybdeid cubomedusae using in situ and citizen science data. Photos of carybdeids with symbionts and prey in the Philippines were obtained from local scuba diver-photographers. These photos were authenticated using digital image analyses and cubozoan literature records. Here, only 18.8% ( n = 6) of the recorded carybdeids engaged in ectosymbiosis with “hitchhikers” (i.e., symbionts exhibiting phoresy or swimming with carybdeids). The majority (81.3%) of the carybdeids were “anglers”, consuming a variety of prey such as fishes, crustaceans, bristleworms, and squids. Alatina alata had the highest prey diversity (fish, squid, shrimp, bristleworms, crab megalopa, mantis shrimp), while Carukiidae members ( Malo spp., Morbakka virulenta ) were recorded to consume fish only, suggesting predominant piscivory by these carybdeids. Ectosymbiont taxa were also identified as prey, suggesting that these interactions exist in a symbiosis-predation continuum. Our study highlights the significance of citizen science in expanding our knowledge in the diet and ecology of cryptic and sporadically distributed organisms like carybdeid cubozoans and their inter-species interactions.

Molecular signatures reveal intra-species divergence, undetectable by traditional morphology, in the deadly box jellyfish, Chironex yamaguchii (Cubozoa; Chirodropidae) of Western Pacific - Sheldon Rey Boco; Christine Gloria Grace Capidos; Raffy Jay Fornillos; Phuping Sucharitakul; Jonathan W. Lawley; Dennis Talacay; Allen G. Collins; Ian Kendrich Fontanilla; Joseph Elliz Comendador; Facundo Rey M. Ladiao (Regional Studies in Marine Science, 2025)

Blooms of the dragon thimble jellyfish, Linuche draco, sometimes co-occur with marine heatwaves - Christine Gloria Grace Capidos; Sheldon Rey Boco; André C. Morandini (Marine Biodiversity, 2024)

Observations on the specific associations found between scyphomedusae and commensal fish and invertebrates in the Philippines - Sheldon Rey Boco; Ephrime B. Metillo (Symbiosis, 2018)